2019
DOI: 10.1186/s12302-019-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of chemicals are important drivers of impacts on ecological status in European surface waters

Abstract: The ecological status of European surface waters may be affected by multiple stressors including exposure to chemical mixtures. Currently, two different approaches are used separately to inform water quality management: the diagnosis of the deterioration of aquatic ecosystems caused by nutrient loads and habitat quality, and assessment of chemical pollution based on a small set of chemicals. As integrated assessments would improve the basis for sound water quality management, it is recommended to apply a holis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…These substances, however, can vary seasonally and regionally, which was also observed in this study. Therefore, even if only a few substances are the main contributors to the mixture toxicity, a high number of substances need to be analysed in order to obtain a comprehensive overview of the mixture risks in surface waters [36,37].…”
Section: Drivers Of Mixture Toxicitymentioning
confidence: 99%
“…These substances, however, can vary seasonally and regionally, which was also observed in this study. Therefore, even if only a few substances are the main contributors to the mixture toxicity, a high number of substances need to be analysed in order to obtain a comprehensive overview of the mixture risks in surface waters [36,37].…”
Section: Drivers Of Mixture Toxicitymentioning
confidence: 99%
“…Although the WFD was published in 2000, a good water quality status was not yet reached in 2012 and 2018 in a large fraction of Europe's surface waters [5,12]. Chemical pollution poses a lasting and diversifying problem to surface water quality [7], together with the aforementioned other stressors [13].…”
Section: Challengementioning
confidence: 99%
“…The diagnostic methods are summarized and characterized in the other SOLUTIONS Policy Briefs. For example, methods can be selected for early-stage exploratory assessments on the presence of chemicals [19], via refined component-and effect-based diagnostic approaches of impacts [20,21] to specific biological quality elements [22] and the ecological status [13], up till integrated modeling [23]. The methods cover the full array of the DPSIR-causal approach (Fig.…”
Section: Versatile Tools and Servicesmentioning
confidence: 99%
“…1) as well as several Spanish river basins and a number of additional field sites all over Europe and discussed with European and national agencies, international river commissions and many more important stakeholders. By integrating the SOLU-TIONS monitoring and modeling tools with multiple stress investigations carried out in the MARS project [14], it could be shown that mixtures of chemicals are actually important drivers of impacts on the ecological status in European surface waters [15].…”
Section: Open Accessmentioning
confidence: 99%